Advanced fibre optic sensors developed using femtosecond laser inscription - Theodosiou, Antreas (Department of Electrical Engineering and Computer Engineering and Informatics,Faculty of Engineering and Technology, Cyprus University of Technology, 2018)
Currently optical fibres are widely used for telecommunications and sensing applications due to their immunity to electromagnetic fields, and their light weight and small design. In particular for sensing purposes, different types of specialised fibres have been development either with special designs, such as microstructure patterns or using different kinds of materials. In this way, the sensitivity of the fibres can be enhanced or become unresponsive to specific parameters. However, not all the speciality fibres are photosensitive and efficiently processed with conventional UV lasers to manufacture sensing structures; as a result, most of the ‘alternative’ material or designs fibres are not fully exploited.On the other hand, the femtosecond lasers modify materials using a different principle. The material photosensitivity is not required to induce refractive index changes in the fibres, indeed minimising linear absorption is desirable and the greater the transparency of the material the better for femtosecond laser processing. In this case it is multi-photon absorption that occurs at the laser focus that is important for laser-induced material modifications. In this thesis, we present the development and manufacturing of advanced fibre optic sensors using a femtosecond laser operating at 517 nm. A wide range of different optical fibres processed allows for the fabrication of not only fibre Bragg grating (FBG) sensors but also chirped gratings, Fabry-Perot cavities, and Mach-Zehnder interferometers (MZIs).I summarise several examples that a unique to femtosecond laser inscription. The precise and accurate control of the inscription parameters during the fabrication of sensors in a multi-mode optical fibre can lead to control of the coupling between a Bragg grating and the higher order modes of a low loss polymer optical fibre (POF). A result is that we are able to inscribe single-peak FBG sensors as an array in the multi-mode optical fibre. We demonstrate this by inscribing FBGs in a low loss POF, in which it is not possible to inscribe gratings using conventional UV-laser sources, and hence demonstrate applications using polymer fibres over several tens of meters, which exceed the operating length of POF-based sensors by three orders of magnitude at an operating wavelength of 1550 nm.
Keywords: Femtosecond Laser; Fibre Bragg Gratings; Polymer Fibres; Waveguides; Optical Fibre Sensing